(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract: The research aims to demonstrate the extent to which the internal auditor in the General Tax Authority adheres to international performance standards. International performance standards work to determine the formula in which the audit function is exercised and are considered a measure of the professional performance required of the auditor. These standards describe the activity and nature of the internal audit work and how to implement each task. Its tasks are by measuring the performance of the internal auditor. For the purpose of achieving the research objective, reliance was placed on the checklist related to international performance standards in collecting data and information, for the purpose of demonstrating the extent of application and documentation through adherence to international performance standards, and knowing the strengths and weaknesses, and from here the research problem emerged, as Through our field training at the General Tax Authority, it was revealed that it lacks effective auditing procedures that confirm respect and implementation of the legislative framework and internal organization for the conduct of various operations. This is because internal auditing is a mechanism for early detection and a prior warning tool for possible errors and deviations during the completion of these activities. The main question was formulated. For the research problem (what is the reality of internal auditing in the General Tax Authority, and what challenges does it face?) The research relied on the descriptive approach in the theoretical aspect and the analytical approach in the practical aspect, as the checklist for international performance standards was adopted, for the purpose of measuring the level of their application in accordance with the standards in the Authority and diagnosing the size of the gap and determining its causes, as well as interviews with officials in the Authority. The most prominent findings of the research were that the level of application and documentation of this standard reached (zero%), meaning a gap of (100%). The most important recommendations were the necessity of implementing performance standards by The Internal Audit Department at the General Tax Authority because of its impact in raising the efficiency of internal audit and the effectiveness of its procedures.